Estrategias Didácticas para mejorar los procesos enseñanza-aprendizaje de Estudios Sociales con estudiantes de EGB media. - Arroyo Fabara, Lizeth Karina (2022)
The present research work was framed in the problem detected in the Tirso de Molina Fiscal Missionary Educational Unit of the city of Ambato. The objective was to propose different didactic strategies to improve the learning of Social Sciences, since as such it is one of the branches of education focused on knowing sociological aspects inherent to the development of the human being. For this research, we worked with a methodological design framed in the qualitative paradigm, combined with the modality of applied research. There was the random participation of 35 students and 4 teachers, using the survey and interview as research instruments in which the development of a proposal was proposed that consisted of improving the teaching-learning process with the use of guided visits to interactive museums on the 3600 platform as a teaching resource, this activity has a micro-curricular planning, focused on improving the dimensions of learning. With the application of this proposal, the results indicated that it has a great acceptance for both students and teachers of the Tirso de Molina Fiscomisional Educational Unit of the city of Ambato, which is why it can be affirmed that its implementation is feasible.